Standardization in ayurvedic medicine: still a far cry - Shubhangi, Pawar; Patil, D A (Journal of Experimental Sciences, 2012)
Plants are known to the common people by their indigenous system of nomenclature. Sanskrit is one such rich language. Sanskrit plant names convey all-pervasive information about Indian culture. The plant names in Sanskrit is one way of determining plant species and thereby a drug used in Ayurvedic system. About 20 Sanskrit plant names are explained etymologically and their help in identifying the taxon under consideration. These help decipher the taxa/drugs adequately. There are also instances wherein it is helpless as they point out different sources of the Ayurvedic drugs. Standardisation of a drug is a must and one has to go not simply by literature but by plant material in hand. Attempts to identify the Ayurvedic drugs are far from the main goal of standardization which is the crying need of the hour.